A new perspective for urban development boundary delineation based on SLEUTH-InVEST model. (December 2017) - Liu, Jiaxun; Zhang, Ge; Zhuang, Zhuzhou; Cheng, Qianwen; Gao, Yu; Chen, Tan; Huang, Qiuhao; Xu, Lang; Chen, Dong
Abstract: The delineation of urban development boundaries is a policy measure to manage the growth of urban space in an orderly fashion. By studying the municipal districts of Changzhou City, this study proposes a delineation model of Urban Development Boundary (UDB), which considers ecological space quality. First, we developed the SLEUTH model in accordance with the redefined targets of the General Land-use Plan of Changzhou City; we applied the model to generate urban expansion for 2020 and arrived at the estimated limits of Changzhou's urban expansion boundaries. Second, based on these approximations, we developed an InVEST model to evaluate the ecological space quality of the study area. By analysing the spatial coordination of hypothetical urban expansion boundaries and its ecological space quality, we delineated an urban development boundary for the study area. This delineation method can help solve spatial incongruities between urban development and ecological conservation, and balance economic development and environmental protection. The UDB delineation model proposed in this study incorporates the interrelations between ecological conservation and urban development; the results obtained thus provide a theoretical and technological foundation for future urban planning and construction management in Changzhou City. Highlights: This study proposes the SLEUTH-InVEST model to portray urban development boundaries. The model creates urban expansion projections considering ecological space qualities. This resolves spatial disparity between urban development and ecological conservation. A balance between economic development and environmental protection can be attained.